The transformation of the temple in the Fourth Gospel - Welzen, Huub (HTS teologiese studies, 2016)
In at least two stories of the Fourth Gospel the transformation of the temple is an explicit theme. In the story of the cleansing of the temple the narrator comments that Jesus spoke of the temple of his body. In the dialogue with the Samaritan woman Jesus explains that God is no longer worshipped at mount Gerizzim or in Jerusalem, but in spirit and truth. In this article I will try to describe some aspects of this transformation against the background of the conflict between the Johannine congregation and the synagogue. As the dwelling place of God the temple is a holy place. Characteristic for the temple that Jesus is, is the mutual indwelling of God and Jesus and the mutual connection of Jesus and his disciples. The two mutual relations make it possible that the disciples come into contact with God. In the new temple that Jesus is, Jesus himself is the sacrifice of atonement. This atonement restores the relation of God and the believers. In the situation that is characterised by the absence of Jesus, the function of Jesus is taken over by the spirit of truth. That God is worshipped in spirit and truth makes a new inclusiveness and universality possible, where the conflict between the ‘Jews’ and Jesus’ disciples is unsolvable because of the exclusive claims of the conflicting parties.